STATE OF THE ART OF CANCER CARE DELIVER Y IN MOSCOW - A. P. Gnatyuk; Yu. V. Samsonov (Исследования и практика в медицине)
Abstract:The globally increased concern with the situation, existing in oncology, is conditioned by a steady incidence rate of malignant neoplasms, having a tendency to its growth. Annually over 7 million people die in the world due to cancer, by 2020, according to WHO estimations, this index will increase to 10 million. By the end of the 2013 report year patient population with cancer, registered in cancer care facilities of the Russian Federation, is 3 098 855 (2 995 566 in 2012), i. e. 2,1% of the population of the country. The system of cancer care delivery to the population in the Russian Federation and in Moscow is aimed at an early diagnostics and prevention of malignant neoplasms. Municipal cancer care service establishes the patients’ routes at suspicion on oncological disease and determines the functions of all links of health care for this type of patients. Stateof-the-art delivery of oncological specialty care has been built up with account of modern demands and is functionally structured in accordance with tree-level municipal health care system.